Black or white coffee before anaesthesia?: A randomised crossover trial. Issue 6 (June 2016) - Larsen, Birgit; Larsen, Lars P.; Sivesgaard, Kim; Juul, Svend
Abstract : BACKGROUND: In current preoperative fasting guidelines, coffee with milk is still regarded by many as solid food. Evidence on the consequences for gastric volume of adding milk to coffee 2 h before anaesthesia is still weak. OBJECTIVES: The aim of this study was to compare the gastric volume by MRI in healthy volunteers after drinking coffee with and without added milk. DESIGN: A randomised crossover trial where all participants were exposed to three coffee and milk mixtures performed as a noninferiority study with a predefined noninferiority limit of 12 ml. SETTING: Department of Day Surgery and Department of Radiology, Aarhus University Hospital, Aarhus, Denmark. The study was conducted between August 2013 and February 2014. PARTICIPANTS: Total 32 healthy volunteers, aged 18 to 71 years. INTERVENTIONS: The participants fasted for 6 h for solid food, and 2 h before the MRI examination of gastric volume, each participant ingested one of three coffee mixtures: 175 ml coffee, including either 0 or 20 or 50% full fat milk. Each participant was studied by MRI three times separated by a minimum time interval of 2 days. The order of coffee mixture ingested was determined by random allocation. MAIN OUTCOME MEASURE: Gastric volume as measured by MRI. RESULTS: The mean gastric volume for black coffee was 27.8 ml, for coffee with 20% milk 17.9 ml and for coffee with 50% milk 20.6 ml. Compared to black coffee, the gastric volume for 20% milk was significantly decreased with a difference of −10.0 ml (95% confidence interval, −18.2, −1.8), and for 50% milk it was insignificantly decreased, −7.2 ml (95% confidence interval, −17.4, +2.9). The upper confidence interval for the difference in gastric volume between the 'no milk added' group and each 'milk added' group did not reach the noninferiority limit of 12 ml. CONCLUSION: The study provides evidence that adding up to 50% full fat milk to coffee leads to no or only a minimal increase of the gastric volume 2 h later. The results support a liberalisation of policy on the addition of milk to hot drinks before planned anaesthesia. TRIAL REGISTRATION: www.Clinicaltrials.gov identifier: NCT02361632. Abstract : Supplemental Digital Content is available in the text